Iowa RBA, September 11-14, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for September 11-14, 1995. Highlights of the update include sightings of a juvenile White Ibis, Red-necked Phalarope, Sabine's Gull, California Gull, Laughing Gull, Black-throated Blue Warblers and Sandhill Cranes. Contains numerous reports of Red-breasted nuthatch sightings. Also included are handwritten notes for the next week's update with sightings of a Yellow Rail and American Pipits. Epson - sheet feed/flatbed